2001
DOI: 10.1118/1.1386780
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effectiveness of a longitudinal magnetic field in reducing underdosing of the regions around upper respiratory cavities irradiated with photon beams—A Monte Carlo study

Abstract: The problem of underdosing lesions adjacent to upper respiratory cavities and a proposal to correct it are presented in this work. The EGS4 Monte Carlo code was used to simulate a 6 MV x-ray beam passing through a block of tissues with air cavities 2, 4, and 6 cm wide. The geometry used approximates the tracheal geometry used by previous researchers who investigated the underdosing phenomenon. A uniform longitudinal magnetic field of 0.5 T strength is used to reduce secondary electron outscatter caused by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…However, the magnetic field effect on photon beams was not reported until some 40 years later, when Bielajew [2] showed reduction of the penumbral width using strong longitudinal magnetic fields. A modest longitudinal magnetic field was also shown to minimize potential target underdosing for tumors located in or near low‐density regions such as the lung or trachea [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…However, the magnetic field effect on photon beams was not reported until some 40 years later, when Bielajew [2] showed reduction of the penumbral width using strong longitudinal magnetic fields. A modest longitudinal magnetic field was also shown to minimize potential target underdosing for tumors located in or near low‐density regions such as the lung or trachea [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Although some scholars advocate adjustment of the radiation dose, (27) most advocate irradiation from two fields or irradiation with the same center from several fields instead. The latter methods allow variation of dose to be reduced to 4%, which meets the requirement (Report ICRU 24) that the total uncertainty of dose in the target region must be less than 5% 21 , 28 , 29 . In order to reduce the influence of metal implants on the dose of radiation therapy, the treatment planning system (TPS) is usually employed for simulation calculation (30) .…”
Section: Discussionmentioning
confidence: 99%
“…Wadi-Ramahi et al, suggested that a uniform longitudinal magnetic field of 0.5 T strength could be used to reduce secondary electron out-scatter caused by the presence of an air gap to improve the dose at the distal surface of air cavities. [34]…”
Section: Introductionmentioning
confidence: 99%